SIGNIFIKANSI PENDIDIKAN KARAKTER DALAM DUNIA PENDIDIKAN - Sahrudin, Sahrudin; Herlambang, Ricoh (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Character education is essential not only in schools but also at home and within the broader social environment. Today, character education is crucial not just for children from early childhood to adolescence, but also for adults. It is imperative for the future of this nation. Consider the competition that will arise in the coming years. It will undoubtedly be a challenge for both parents and society today. In the future, children will compete with peers from around the globe. Even those of us still in the workforce will face similar challenges. The demand for quality human resources in the coming millennium clearly necessitates strong character, as character is fundamental to achieving individual success.